2015
DOI: 10.1016/j.tet.2015.01.035
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenolic C-glucosidic ellagitannins present in oak-aged wine inhibit HIV-1 nucleocapsid protein

Abstract: HIV-1 nucleocapsid protein (NC) is a nucleic acid chaperone implicated in several steps of the virus replication cycle and an attractive new target for drug development. In reverse transcription, NC destabilizes nucleic acid secondary structures and catalyzes the annealing of HIV-1 TAR RNA to its DNA copy (cTAR) to form the heteroduplex TAR/cTAR. A screening program led to the identification of the plant polyphenols acutissimins A and B as potent inhibitors of NC in different assays. These two flavano-ellagita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 43 publications
2
19
0
Order By: Relevance
“…The orientation of the hydroxyl group at the C1 position of the C -glycosidic ETs, such as vescalagin and castalagin, has been shown to affect both their physicochemical properties as well as bioactivities. ,, In the present study, the orientation of the hydroxyl group at the anomeric carbon affected both the ICF AVER and the ICF INIT values as could be seen when comparing monomer pairs 17 versus 18 , 19 versus 20 , 21 versus 22 and the dimers 29 – 32 . In the monomers, α-orientation resulted in more efficient complex formation in all three pairs, the effect being greatest between 17 and 18 (ICF AVER 0.35 → 0.86, ICF INIT 0.51 → 0.27) and lower between 19 and 20 (ICF AVER 0.50 → 0.71, ICF INIT 0.50 → 0.37) and between 21 and 22 (ICF AVER 0.45 → 0.60, ICF INIT 0.41 → 0.36).…”
Section: Results and Discussionmentioning
confidence: 50%
“…The orientation of the hydroxyl group at the C1 position of the C -glycosidic ETs, such as vescalagin and castalagin, has been shown to affect both their physicochemical properties as well as bioactivities. ,, In the present study, the orientation of the hydroxyl group at the anomeric carbon affected both the ICF AVER and the ICF INIT values as could be seen when comparing monomer pairs 17 versus 18 , 19 versus 20 , 21 versus 22 and the dimers 29 – 32 . In the monomers, α-orientation resulted in more efficient complex formation in all three pairs, the effect being greatest between 17 and 18 (ICF AVER 0.35 → 0.86, ICF INIT 0.51 → 0.27) and lower between 19 and 20 (ICF AVER 0.50 → 0.71, ICF INIT 0.50 → 0.37) and between 21 and 22 (ICF AVER 0.45 → 0.60, ICF INIT 0.41 → 0.36).…”
Section: Results and Discussionmentioning
confidence: 50%
“…Having demonstrated that B-CePs bind and stabilize the RNA substrate of NC, we performed a high-throughput screening (HTS) to analyze the in vitro ability of the tested B-CePs to inhibit NC-mediated melting of the TAR RNA hairpin construct [ 14 , 16 , 17 , 18 , 19 ]. This assay is based on the doubly labeled TAR construct used above in the FQA experiments and is extensively employed to screen for inhibitors of NC melting activity [ 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…The biologically relevant domain of TAR is the substrate of multiple viral RNA-binding proteins, playing a critical role in several biological processes within the viral replication cycle [ 8 , 9 , 10 , 11 , 12 , 13 ]. In particular, we became interested in TAR as the substrate of the HIV-1 nucleocapsid (NC) protein [ 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The stoichiometry and strength of the binding interactions between NC and the various compounds were evaluated by using electrospray-ionization mass spectrometry (ESI-MS) under non-denaturing conditions. The detection of intact non-covalent complexes, like those formed by these ligand-NC systems, can be achieved by appropriately tuning the ion source conditions to minimize the desolvation energy [39]. This type of analysis can reveal the accurate partitioning between any free and bound species in solution, which can provide the binding constant of a given complex [40].…”
Section: Evaluation Of Binding Propertiesmentioning
confidence: 99%